2015
DOI: 10.5665/sleep.5226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sleep and Circadian Disruption on Energy Balance and Diabetes: A Summary of Workshop Discussions

Abstract: A workshop was held at the National Institute for Diabetes and Digestive and Kidney Diseases with a focus on the impact of sleep and circadian disruption on energy balance and diabetes. The workshop identified a number of key principles for research in this area and a number of specific opportunities. Studies in this area would be facilitated by active collaboration between investigators in sleep/circadian research and investigators in metabolism/diabetes. There is a need to translate the elegant findings from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 122 publications
(142 reference statements)
1
109
0
5
Order By: Relevance
“…Existing first-line drug therapies for metabolic disease and type 2 diabetes, such as the commonly used insulin sensitiser, metformin, are known to modulate molecular clock function in insulinsensitive tissues [166][167][168]. Sleep disturbances predispose individuals to obesity and diabetes, and obesity predisposes individuals to sleep disturbances, instigating a vicious cycle [18,169]. So what can we do about this?…”
Section: Therapeutic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing first-line drug therapies for metabolic disease and type 2 diabetes, such as the commonly used insulin sensitiser, metformin, are known to modulate molecular clock function in insulinsensitive tissues [166][167][168]. Sleep disturbances predispose individuals to obesity and diabetes, and obesity predisposes individuals to sleep disturbances, instigating a vicious cycle [18,169]. So what can we do about this?…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…Recent efforts have been made to differentiate the effects of circadian disruption or circadian misalignment from other forms of sleep disturbance [18,20,21,92]. Evidence from a clinical study of circadian disruption in controlled-laboratory conditions revealed that exposure to misalignment, as occurs during shift work or chronic jet lag, leads to hyperinsulinaemia, hyperleptinaemia and misaligned cortisol rhythms [21].…”
Section: Sleep Disturbance Circadian Disruption and Altered Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, evaluation and treatment of sleep-disordered breathing may have potential to improve fertility in this population of women. Further, as sleep deprivation also impairs glucose homeostasis [5], adequate sleep duration may also be crucial in this setting.…”
Section: Polycystic Ovary Syndrome and Obstructive Sleep Apneamentioning
confidence: 99%
“…OSA has also been linked to metabolic syndrome, hypertension, stroke, and cancer. Animal models that mimic conditions of OSA show altered metabolic, inflammatory, and autonomic changes with associated autonomic risk (85). The impact of the circadian system on OSA is unclear, but it may influence apnea occurrence and duration in the early morning compared with late afternoon.…”
Section: Osamentioning
confidence: 99%